Impact of Constructive Leadership Styles on Employee Well-being, with the Mediating Role of Autonomy Support - Tariq, Amina; Akhtar, Sidra; Ashraf, Nyela (Annals of Human and Social Sciences, 2023)
The aim of this research work is to investigate the link between the constructive leadership style like transformational and charismatic leadership style and the well-being of the employees with the mediating effect of autonomy support. Leaders have a crucial role in managing organizational interventions, which are efforts to promote employee health and well-being by changing the way work is organized, created, and managed. During this quantitative research, we analyzed the data that was collected from 436 workers who were employed in a different Free Zones in Pakistan. The data were gathered using questionnaires for surveys. According to our findings, transformational and charismatic leadership have a significant effect on the well-being of employees, whereas mediating effects of autonomy support is also present between constructive leaderships and employee well-being. Future researchers should include a diverse sample of enterprises in Free Zones to study these variables, also categorize the Free Zones based on size, ownership, and control.